Nebulized enriched heparin to treat no critical patients with Sars-Cov-2: Triple-blind clinical trial. Issue 51 (23rd December 2021) - Bertanha, Matheus; Rodrigues, Lenize da Silva; Mellucci Filho, Pedro Luciano; Moroz, Andrei; Pardini, Maria Inês de Moura Campos; Sobreira, Marcone Lima; Durigon, Edison Luiz; Machado, Rafael Rahal Guaragna; Grotto, Rejane Maria Tommasini; Lima, Marcelo Andrade de; Nader, Helena Bonciani; Moraes, Marli Leite de; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19) is a viral respiratory disease that spreads rapidly, reaching pandemic status, causing the collapse of numerous health systems, and a strong economic and social impact. The treatment so far has not been well established and there are several clinical trials testing known drugs that have antiviral activity, due to the urgency that the global situation imposes. Drugs with specific mechanisms of action can take years to be discovered, while vaccines may also take a long time to be widely distributed while new virus variants emerge. Thus, drug repositioning has been shown to be a good strategy for defining new therapeutic approaches. Studies of the effect of enriched heparin in the replication of severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) in vitro assays justify the advance for clinical tests. Methods and analysis: A phase I/II triple-blind parallel clinical trial will be conducted. Fifty participants with radiological diagnosis of grade IIA pneumonia will be selected, which will be allocated in 2 arms. Participants allocated in Group 1 (placebo) will receive nebulized 0.9% saline. Participants allocated in Group 2 (intervention) will receive nebulized enriched heparin (2.5 mg/mL 0.9% saline). Both groups will receive the respective solutions on a 4/4 hour basis, for 7 days. The main outcomes of interest will be safety (absence of serious adverse events) and efficacy (measured by the viral load). Protocols will be filled on a daily basis, ranging from day 0 (diagnosis) until day 8. Abstract : Supplemental Digital Content is available in the text